1983
DOI: 10.1159/000206881
|View full text |Cite
|
Sign up to set email alerts
|

Hypergammaglobulinemic Purpura of Waldenström: Characterization of Circulating Immune Complexes

Abstract: Circulating immune complexes were detected in the sera of 7 patients with hypergammaglobulinemic purpura of Waldenström by the following methods: KgB-SP, mRF-LIA, Cc test, C1qBA. Analytical ultracentrifugation showed intermediate complexes between 7S and 19S (16S-19S); simple immunodiffusion of the complexes, purified by 2.5% PEG precipitation, revealed the presence of IgG3, IgA, IgM, C1q, C3 and C4. Constant high titers of rheumatoid activity in the sera in toto and after purification, and normal serum comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…This provides one possible explanation for the absence of synovitis in subjects with HPW. ‘Intermediate’ complexes, consisting of self‐associated RF, exist in HPW sera, but in patients with no arthritis they were found to be restricted to IgG3 29 . This would be consistent with an inability of IgG3 RF dimers to induce signalling via FcγRIIIa.…”
Section: Rf and Inflammationmentioning
confidence: 62%
“…This provides one possible explanation for the absence of synovitis in subjects with HPW. ‘Intermediate’ complexes, consisting of self‐associated RF, exist in HPW sera, but in patients with no arthritis they were found to be restricted to IgG3 29 . This would be consistent with an inability of IgG3 RF dimers to induce signalling via FcγRIIIa.…”
Section: Rf and Inflammationmentioning
confidence: 62%
“…20 In the treatment of HGPW, it is most likely that MMF's immunosuppressive affects provided benefit by disrupting the formation of immune complexes, which are thought to be the causative factor. 18,19 In our patient, there was a demonstrated decrease in both the gamma globulin and sedimentation rate after therapy was initiated, which was most likely a result of the inhibition of both T and B lymphocytes. There was also a significant improvement in the patient's symptoms that coincided with the normalization of laboratory values.…”
Section: Mycophenolate Mofetil Treatment Of a Patient With Hyperglobumentioning
confidence: 62%
“…[2][3][4][5][6][7][8]10 In support of an autoimmune process, several individual cases and studies have demonstrated the presence of immunoglobulin within blood vessel walls and circulating immune complexes as the most likely cause of HGPW. 8,[10][11][12]18,19 MMF is an immunosuppressive agent with a mechanism of action that has been well described. [13][14][15][16] It has been used to treat a variety of cutaneous inflammatory/autoimmune conditions (Table I) including autoimmune blistering disorders and cutaneous collagen vascular diseases.…”
Section: Mycophenolate Mofetil Treatment Of a Patient With Hyperglobumentioning
confidence: 99%